Foreign Investment Penetration Loophole on the Negative Investment List (DNI) Related to Shares Pledge in PT GLOBAL JET EXPRESS - P, Ign Hendrawan (Dinasti Research, 2025)
Law Number 25 of 2007 concerning Investment in Article 33 regulates the prohibition on borrowing names in share ownership for the establishment of a Limited Liability Company, in accordance with the provisions of statutory regulations. However, in the Republic of Indonesia Law Number 40 of 2007 concerning Limited Liability Companies in Article 60 paragraph (2) it states that shares can be pledged with a pledge or fiduciary guarantee as long as it is not specified otherwise in the articles of association. The article does not provide further qualifications of special requirements where share pledges can be made. This study examines the correlation between Article 60 of Law Number 40 of 2007 concerning Limited Liability Companies with Article 33 of Law Number 25 of 2007 concerning Investment, specifically focusing on PT Global Jet Express and J&T Global Express Limited concerning pledges and share ownership, specifically discussed whether Article 60 of Law Number 40 of 2007 concerning share pledges creates a loophole for foreign investment penetration in the Negative Investment List. This study further investigates whether the practice of PT Global Jet Express share pledges has weakened Article 33 paragraph of Law Number 25 of 2007 concerning Investment. This study aims to determine whether adjustments to Article 60 of Law Number 40 of 2007 are needed to support the function of the DNI in protecting the Indonesian economy and to provide more business opportunities for domestic investors